Comparative cytogenetic studies in species of the subfamily Callichthyinae (Teleostei: Siluriformes: Callichthyidae) - Shimabukuro-Dias, Cristiane Kioko [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Firenze University Press, 2005)
In the present study, the karyotype of three species (nine populations) of the Callichthyinae subfamily were investigated with the objective of better understanding the pattern of relationship among the genera that compose the subfamily. Among the four populations of Callichthys callichthys studied, two showed 2n=56 chromosomes and two 2n=58 chromosomes. Up to eight additional microchromosomes were observed in the sample from Marilia. The three populations of Hoplosternum littorale displayed the same number of chromosomes, 2n=60, and karyotypic constitution, 6M+2SM+52A. The two populations of Megalechis personata showed 2n=62 chromosomes and similar karyotypic formulae, 8M+54A and 6M+2SM+54A. Terminal Ag-NORs were found in one chromosome pair of C. callichthys, H. littorale, and M. personata from Itiquira, and in two pairs in M. personata from Rio Branco. The populations of C. callichthys showed C-band positive segments in centromeric and pericentromeric position and the populations of H. littorale and M. personata exhibited C-band positive segments in centromeric and/or interstitial position. Contrarily to the extensive chromosome rearrangements verified in the Corydoradinae subfamily, in the Callichthyinae subfamily a small number of changes seems to have occurred in its karyotypic evolution.
Keywords: Ag-NOR; C-band; Chromosomes; Fish cytogenetic; Karyotypic evolution; Callichthyidae; Callichthys callichthys; Hoplosternum littorale; Marilia; Megalechis personata; Siluriformes; Teleostei